SPEI-Based Spatiotemporal Analysis of Drought in Haihe River Basin from 1961 to 2010 - Meijian Yang; Denghua Yan; Yingdong Yu; Zhiyong Yang (Advances in Meteorology)
Under the background of climate change, the monthly accumulated precipitation and monthly averaged temperature of 47 meteorological stations in and around Haihe River Basin (HRB) were analyzed using Standardized Precipitation Evapotranspiration Indices (SPEI) to obtain the temporal variability and spatial distribution of different drought levels during the last 50 years with the support of GIS. The results show that (1) from 1961 to 2010 the drought frequency and degree in annual and seasonal scale are rising and the affecting areas of all degrees of drought have a temporal variability of increasing trend. The ratios that the influencing area of drought, light drought, moderate drought, severe drought, and extreme drought account for the whole HRB area are increasing with gradients of 0.64%/a, 0.18%/a, 0.31%/a, 0.14%/a, and 0.01%/a, respectively, and (2) there is a climate break point which occurred in 1990; after the comparison of the drought happening probability between 1961 and 1990 and between 1991 and 2010, all degrees of drought occurrence probability have a remarkable rising trend, and the drought concentrating regions moved from the north HRB to the central HRB.